2018
DOI: 10.1136/tobaccocontrol-2018-054244
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of progression of nicotine dependence symptoms in adolescent waterpipe smokers

Abstract: A significant proportion of adolescent waterpipe smokers progressed on ND. Venue-based policies such as limiting youth access to waterpipe cafés are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Epidemiological studies have shown that WP smoking is associated with increased risks of cardiovascular diseases,6 cancer (lung, oesophageal, head and neck, and gastric),7–10 metabolic syndrome11 and chronic obstructive pulmonary disease (COPD) 12. An additional health risk that is of particular concern for young adults is nicotine dependence, and similar to any other tobacco product is represented in WP smokers by substance addiction behaviours 13–19. In agreement with the health risks identified to date, analytical examination of the components in WP smoke include a mixture of chemicals with known or suspected disease-causative agents that closely resemble those found in cigarette smoke (CS), and in many cases at higher concentrations 20 21.…”
Section: Introductionmentioning
confidence: 83%
“…Epidemiological studies have shown that WP smoking is associated with increased risks of cardiovascular diseases,6 cancer (lung, oesophageal, head and neck, and gastric),7–10 metabolic syndrome11 and chronic obstructive pulmonary disease (COPD) 12. An additional health risk that is of particular concern for young adults is nicotine dependence, and similar to any other tobacco product is represented in WP smokers by substance addiction behaviours 13–19. In agreement with the health risks identified to date, analytical examination of the components in WP smoke include a mixture of chemicals with known or suspected disease-causative agents that closely resemble those found in cigarette smoke (CS), and in many cases at higher concentrations 20 21.…”
Section: Introductionmentioning
confidence: 83%
“…Different cultural and socioeconomic backgrounds as well as use of other tobacco products can be determinants regarding the consumption of WP by adolescents [ 15 , 16 , 17 ]. The aromatic taste of WP tobacco (e.g., apple, cherry, melon) appeals to young people and can be associated with a more pleasant, longer smoking experience which leads to increased nicotine exposure and dependence potential [ 18 , 19 , 20 ]. Furthermore, the consumption of WP is associated with other harmful health effects similar to those associated with cigarette smoking [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…E-cigarette use and waterpipe tobacco smoking are of growing concern due to the adolescents’ exposure to nicotine. There is often a misconception that nicotine/tobacco dependence cannot be developed by waterpipe tobacco smoking 5 . Furthermore, nicotine exposure and nicotine dependence specific to e-cigarettes among adolescents are severe public health issues 6 .…”
Section: Introductionmentioning
confidence: 99%